Examining the Indian Farmer Suicides through the Social and Environmental Justice Lens - Yogita Abichandani; Juanita Johnson-Bailey (Adult Education Research Conference, 2010)
Approximately 200,000 farmers have committed suicide in India over the last decade. A majority of them are the ones who have been failed by the non- yield of genetically modified cotton per hectare and are dependent on these crops for their daily livelihood. The GM cottonseeds represent the hegemony and oppression of the farmers propelled by the globalization movement. This paper provides an understanding that the social movements against the GM seeds are in fact movements pointing towards the social and environmental injustices and seeks to understand the role adult education can play in addressing the social and environmental injustice.
Keywords: Indian farmer suicides; Social justice; Environmental Justice; Adult education